Pengaruh Model Pembelajaran Project Based Learning (PjBL) Melalui Pendekatan Etnomatematika Terhadap Kemampuan Berpikir Kritis Siswa Kelas III Sekolah Dasar - Erik Wijaksono; Hafidur Rahman; Mohammad Fahmi Syauki; Syamsul Arifin (Kampus Akademik Publiser, 2025)
This study aims to analyze the influence of the Project Based Learning (PjBL) learning model through an ethnomathematical approach on the critical thinking ability of grade III students on flat building materials. This research is based on the importance of critical thinking skills in 21st century education, especially in mathematics learning which is often focused on theories and formulas. The method used was an experiment with a non-equivalent control group design, which involved two classes at SDN Ambunten Timur II, namely an experimental class that applied PjBL and a control class that used conventional learning. Data were collected through pretest and posttest which were analyzed using t-tests to test hypotheses. The results showed that the application of ethnomathematics-based PjBL significantly improved students' critical thinking skills, with the average N-Gain of the experimental class reaching 10.5 or 35.5% higher compared to conventional learning. This research is expected to contribute to the development of innovative learning strategies that are relevant to the local cultural context, as well as a reference for educators in improving mathematics learning in elementary schools.